2018
DOI: 10.1177/2396987318771174
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying unmet needs in long-term stroke care using in-depth assessment and the Post-Stroke Checklist – The Managing Aftercare for Stroke (MAS-I) study

Abstract: Introduction: Detailed data on the long-term consequences and treatment of stroke are scarce. We aimed to assess the needs and disease burden of community-dwelling stroke patients and their carers and to compare their treatment to evidence-based guidelines by a stroke neurologist. Methods: We invited long-term stroke patients from two previous acute clinical studies (n ¼ 516) in Berlin, Germany to participate in an observational, cross-sectional study. Participants underwent a comprehensive interview and exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
2
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 46 publications
3
72
2
8
Order By: Relevance
“…Two-thirds of the clients contacting stroke service points in Berlin are caregivers [34]; this reveals the need to involve the nearest relative in evaluation and support. In the MAS-I study 24% of the caregivers reported moderate to high levels of stroke-related caregiver burden [11]. Several approaches have been suggested to close the gap between inpatient and outpatient care [52][53][54], however, social care has been understudied.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two-thirds of the clients contacting stroke service points in Berlin are caregivers [34]; this reveals the need to involve the nearest relative in evaluation and support. In the MAS-I study 24% of the caregivers reported moderate to high levels of stroke-related caregiver burden [11]. Several approaches have been suggested to close the gap between inpatient and outpatient care [52][53][54], however, social care has been understudied.…”
Section: Discussionmentioning
confidence: 99%
“…The present exploratory analysis is part of the MAS-Istudy, a cross-sectional exploratory study of post rehabilitation patient needs and caregiver burden after stroke [11]. The dataset represents a first step in a more complex project, aiming to gather information on unmet medical and social needs in the long-term aftercare for stroke in the outpatient setting.…”
Section: Study-designmentioning
confidence: 99%
See 3 more Smart Citations